2001
DOI: 10.1128/iai.69.8.4823-4830.2001
|View full text |Cite
|
Sign up to set email alerts
|

Major Outer Membrane Protein Omp25 ofBrucella suisIs Involved in Inhibition of Tumor Necrosis Factor Alpha Production during Infection of Human Macrophages

Abstract: Brucella spp. can establish themselves and cause disease in humans and animals. The mechanisms by which Brucella spp. evade the antibacterial defenses of their host, however, remain largely unknown. We have previously reported that live brucellae failed to induce tumor necrosis factor alpha (TNF-␣) production upon human macrophage infection. This inhibition is associated with a nonidentified protein that is released into culture medium. Outer membrane proteins (OMPs) of gram-negative bacteria have been shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 41 publications
5
87
0
Order By: Relevance
“…suis Omp3a has been shown to be involved in the negative regulation of TNF-␣ production after infection of human macrophages, supporting a role for this protein in Brucella capability to survive within cells (31). Furthermore, we have found recently that bvrS mutants do not stimulate the generation of active forms of small GTPases of the Rho family on cell contact (32), indicating that this two-component system is also necessary for establishing an adequate cross talk with the host cell.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…suis Omp3a has been shown to be involved in the negative regulation of TNF-␣ production after infection of human macrophages, supporting a role for this protein in Brucella capability to survive within cells (31). Furthermore, we have found recently that bvrS mutants do not stimulate the generation of active forms of small GTPases of the Rho family on cell contact (32), indicating that this two-component system is also necessary for establishing an adequate cross talk with the host cell.…”
Section: Discussionmentioning
confidence: 65%
“…mAbs to the following Omps were used (17)(18)(19): Omp10 (A68͞07G11͞C10), Omp16 (A68͞08C03͞ G03), Omp19 (A76͞05C10͞A08, A76͞18B02͞D06), Omp25 (A18͞13D02͞F05, A19͞12B10͞F04, A59͞05F01͞C09, A70͞ 06B05͞A07, A76͞02C12͞C11, A68͞04B10͞F05, A68͞07D11͞ B03, A68͞28G06͞C07), Omp2b (Omp36) (A63͞08D08͞C07, A63͞05A07͞A08, A63͞03H02͞B01, A63͞11E05͞D11, A63͞ 13G02͞C04, A63͞04D11͞G01, A68͞25G05͞A05), and Omp1 (Omp89) (A53͞10B02͞A01). Anti-Omp25 mAbs A18͞13D02͞ F05, A19͞12B10͞F04, and A59͞05F01͞C09 recognize a linear epitope close to the amino-terminal section (amino acids [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. A mAb against the C͞Y epitope was conjugated with peroxidase (20), and was used for LPS detection.…”
Section: Matrix-assisted Laser Desorption Ionization (Maldi)-ms and Pmentioning
confidence: 99%
“…Interestingly, the TNF-α expression in Cat A with the highest level of bacterial load was relatively lower than in the other cats, but Cat A had the highest levels of IL-4 mRNA expression. Following this possibility, outer membrane protein 25 secreted from Brucella suis showed a high sequence homology at amino acids levels to that of a 31-kDa protein (Pap31) of B. henselae, and was demonstrated to be a factor involved in the defect in TNF-α production (7,11).…”
Section: Discussionmentioning
confidence: 99%
“…The use of recombinant protein technology and monoclonal antibodies has shown that the major outer membrane proteins (OMPs) appear to be of limited use as vaccines against smooth B. abortus or B. melitensis infections (Cloeckaetr et al, 2002). Recently, how- (Edmonds et al, 2001(Edmonds et al, , 2002aJubier-Maurin et al, 2001). Pasquevich et al have shown that immunization with OMPs of recombinant Brucella species omp16 or omp19 induces protection against B. abortus infection (Pasquevich et al, 2009).…”
Section: Discussionmentioning
confidence: 99%